(untitled) (Global Journal of Management and Business Research, 2021)
During the 2020-2021 years, it has been necessary for organizations to rethink how they conduct their daily operations in light of COVID-19 restrictions. One of the many activities within organizations is to provide new and recurrent training to their employees. In a similar vein, universities also had to make adaptations to instructional methods. This change provided an opportunity to compare student achievement in two different instructional modalities; one with lectures delivered in a full face-to-face format, and the other with recorded video lectures delivered in online platform. Both formats were conducted in morning and afternoon sessions. Three sets of test results were measured to compare the outcomes between two years. This study had mixed results, two of the three test results sets between the years showed no significant difference between face-to-face and recorded video lectures, while one of the three test results provided evidence that the results were different between instructional methods. The results of this study could provide applicable information to organizations and help to provide a roadmap for providing training in different formats. It is noteworthy that providing instruction in recorded video formats could be less expensive to organizations and also provide more flexibility for employees to fit recurrent t into their daily schedules.